A Review on Hypertension: Practice and Diagnosis - Islam, Mobashara; Chaudhuri, Irfan; Islam, Md. Shahidul; Kamrujjaman, Md. (Journal of Biology and Life Science, 2023)
Among various reasons of raised hypertension, excessive blood pressure is the major one. Hypertension affects over a billion people worldwide, especially the elder people. The International Society of Hypertension (ISH) has extensively developed the practice guidelines to reduce the extent of hypertension caused by high blood pressure (BP) with evidence-based contents for adults, expecting wide range of accessibility and applicability by the physicians from low to high resource settings inclusively. Optimal care defines the evidence-based standard of care while the essential standard refers to the principles of care allowing specification for the deprived settings only. However, the specific portion of this study required to take experts’ opinion when there was a limitation to evidence for undertaking the assessments. This paper evaluates the ways in which we can diagnose hypertension in patients and evaluate the preventive measures and treatment options through lifestyle changes and pharmacological treatments.